De-noising of an experimental acoustic emissions (AE) data using one dimensional (1-D) wavelet packet analysis - Mohd Zul-Hilmi, Mohamad (2009)
Wavelet transformation technique was founded to be more appropriate to analyse the AE signals under such situations. Wavelet transformation technique is used to de-noise the Acoustic Emission data. The de-noised signal is classified to identify a signature based on the type of phenomena. Through various filtering/thresholding techniques, it was found that the original signal was getting filtered out along with noise. There are many type of wavelet that can be used for de-noising data. However, daubechies wavelet is the most wavelet type is use in signal analysis compare to the other wavelet. A signal can be generates using one-dimensional wavelet packet analysis contain in MATLAB to verify the result of de-noising signal.